2002
DOI: 10.1248/cpb.50.960
|View full text |Cite
|
Sign up to set email alerts
|

Formation of an Unusual Dimeric Compound by Lead Tetraacetate Oxidation of a Corynanthe-Type Indole Alkaloid, Mitragynine.

Abstract: In the recent chemical [1][2][3][4][5][6][7][8][9] and pharmacological [10][11][12][13][14][15] studies on the Rubiaceous plant, Mitragyna speciosa, [16][17][18][19][20] which has been traditionally used in tropical areas as a substitute for opium, 21) we have found that mitragynine (1), a major Corynanthe-type indole alkaloid of this plant, exhibited potent analgesic activity mediated by m-and d-opioid receptors. 22)Further, 7-hydroxymitragynine (3), 23) an oxidative derivative of 1, was found as a novel opio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…12). 49) In order to prepare 7-hydroxymitragynine (5) more conveniently, mitragynine (1) was exposed to a hypervalent iodine(III) reagent, PIFA, in aqueous CH 3 CN, expecting the introduction of a hydroxyl group at C7, to give the desired product 5 in 50% yield. 50) Investigation of the minor products in the residue led to the isolation of a novel dimeric compound 63 in 6% yield (Fig.…”
Section: Preparation Of Mitragynine Derivativesmentioning
confidence: 99%
“…12). 49) In order to prepare 7-hydroxymitragynine (5) more conveniently, mitragynine (1) was exposed to a hypervalent iodine(III) reagent, PIFA, in aqueous CH 3 CN, expecting the introduction of a hydroxyl group at C7, to give the desired product 5 in 50% yield. 50) Investigation of the minor products in the residue led to the isolation of a novel dimeric compound 63 in 6% yield (Fig.…”
Section: Preparation Of Mitragynine Derivativesmentioning
confidence: 99%
“…It is currently legal in many parts of the world, and kratom leaves are available for purchase over the Internet. Case studies of fatalities resulting from overdose have been published, although the risk posed by mitragynine remains uncertain, given that simultaneous use or contamination with other substances (including opioids) that may have been involved in the reported deaths. Both mitragynine ( 1 ) and its naturally occurring oxidation product, 7-OH mitragynine (indolenine core) ( 2 ), are opioid antinociceptive agents that have been examined both in vitro and in vivo. Mitragynine pseudoindoxyl ( 3 ), a rearrangement product of 2 with a spiro-pseudoindoxyl core, was first isolated in 1974 by Zarembo et al as a microbial metabolite of 1 by the fungus Helminthosporum sp . Yamamoto et al reported that it acted nonselectively on mu- and delta opioid receptors, while its kappa opioid receptor affinity was negligible .…”
Section: Introductionmentioning
confidence: 99%
“…From the young leaves of M. speciosa, mitragynine (89) was obtained as the major constituent (66.2% based on the crude base) together with its analogues, speciogynine (90), speciociliatine (91), and paynantheine (92). In addition, a new alkaloid, 7α-hydroxy-7H-mitragynine (93), was isolated as a minor constituent, the structure of which was elucidated by spectroscopic analysis and chemical transformation from mitragynine (89) [71].…”
Section: -1 Alkaloids In Mitragyna Speciosamentioning
confidence: 99%
“…In the 13 C-NMR spectrum, the signals corresponding to sp 2 carbons at C14 and C16 resonated at unusually high positions, δ 87.08 and 94.91 ppm, 19 18 Speciogynine (90) Speciociliatine (91) Paynantheine (92) 9 7α-Hydroxy-7H-mitragynine (93) respectively. This unusual phenomenon as well as the novel chemical structure of 102 prompted us to synthesize the new alkaloid in a chiral manner in order to confirm the structure including the absolute configuration due to one chiral center at the C20 position.…”
Section: -1 Alkaloids In Mitragyna Speciosamentioning
confidence: 99%
See 1 more Smart Citation